Penerapan Fitur Recycleview Library Json Dan Metode String Maching Pada Pembangunan Aplikasi Pemasaran Produk Umkm Marga Sakti Berbasis Android - Alvian Febri Wibianto; Muntahanah Muntahanah (UNIVED Press, 2022)
MSMEs (Micro Small and Medium Enterprises) are businesses founded by individuals/individuals/business entities that meet the criteria. MSMEs usually have limited capital, because capital only comes from the business owner or a small group of people who invest capital in the MSME. The string matching method, which is part of the string search process, plays an important role in obtaining data that matches information needs more quickly. In searching for food and beverage category data. So the problem formulation is how to apply the recycleview feature, JSON and the string matching method in developing an Android-based marketing application for MSME products in Margasakti village. With the aim of this research, we can create an Android-based marketing application for MSME products in Marga Sakti Village by implementing a data search process using the string matching method. It is hoped that this application will always be up to date so that this application follows developments in Android-based information technology using the Flutter framework and the Kotlin programming language.